A Review on Causes and Effects of Global Warming (International Journal of Innovative Research in Computer Science & Technology, 2022)
There are many engineer, scientist, and  ecologist are expressing grave worries about the global  climate change. Fossil fuels are used as a source of energy  indefinitely. When carbon dioxide, methane, and nitrogen  oxides are combusted, they release gases that contribute to  the global warming. The warmer the temperature are also  a result of deforestation. The danger of global warming has  always been the biggest threat to the Earth's climate.  Nonetheless, the majority of people are unaware of climate  change and are unaware that it will be a significant issue in  the future years. What the majority of people don't realize  is that global warming is happening right now, and we're  already seeing some of its Withering consequences. It has  and will continue to have a negative impact on ecosystems  and disrupt ecological equilibrium. Because of the perilous  consequences of global warming, a few remedies must be  developed. The article explains global warming, discusses  its origins and risks, and offers a few solutions to this  pressing issue. The majority of people are unaware that  global warming is occurring right now, yet some of its  devastating effects are already being felt. Ecosystems are  being affected in a crucial way, and ecological balance  may be disturbed as a result. Because of the hazardous  consequences of global warming, a few remedies should  be developed. The article discusses global warming, its origins and consequences, and offers possible solutions to  the pressing problem. Solar, wind, hydro, geothermal, and  biomass assets, in particular, would want to be closely  monitored. The placement and usage of renewable energy  sources is one method for slowing the pace of global  warming.
Keywords: Alternative Fossil Fuel; Causes; Climate; Effects; Global Warming Solutions